2019
DOI: 10.30616/ajb.487507
|View full text |Cite
|
Sign up to set email alerts
|

Two new basidiomycete records for the Mycobiota of Turkey

Abstract: Two basidiomycetous taxa, Conocybe velutipes (Velen.) Hauskn. & Svrček and Entoloma ameides (Berk. & Broome) Sacc, were collected from Muradiye district of Van province and reported for the first time from Turkey. The macroscopic and microscopic features of the species were described briefly and the photographs related to their macro and micromorphologies were provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…About 31 species of Conocybe and only one species of Gerronema have been reported from Turkey, and most of them lack molecular evidences (Akçay et al 2018, Çağli et al 2019, Keleş 2020, Sesli et al 2020). It is evident that Turkey's geographic position give rise to a great biological diversity for a variety of macrofungi species.…”
Section: Introductionmentioning
confidence: 99%
“…About 31 species of Conocybe and only one species of Gerronema have been reported from Turkey, and most of them lack molecular evidences (Akçay et al 2018, Çağli et al 2019, Keleş 2020, Sesli et al 2020). It is evident that Turkey's geographic position give rise to a great biological diversity for a variety of macrofungi species.…”
Section: Introductionmentioning
confidence: 99%
“…Marasmius genus contains about 500 species in the family Marasmiaceae (Agaricales, Agaricomycetes, Basidiomycota) and according to presented checklists and the recent studies in Turkey, 12 species have so far been identified belonging to this genus (Kirk et al, 2008;Sesli and Denchev, 2014;Solak et al, 2015;Uzun et al, Akçay et al, 2018;Bozok et al, 2018;Keleş, 2018a;Keleş, 2018b;Sadullahoğlu and Demirel, 2018;Sesli et al, 2018a;Sesli et al, 2018b;Uzun and Kaya, 2018;Altuntaş et al, 2019;Akçay, 2019;Çağlı et al, 2019;Sesli and Bandini, 2019;Acar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pfister, Pulvinula johannis Lantieri and Pulvinula laeterubra (Rehm) Pfister [6,7,8], have been reported from Turkey. Current checklists [9,10] and the latest contributions [11,12,13,14,15,16,17,18,19] indicate that Pulvinula alba hasn't been recorded from Turkey before. Here we present it as the sixth member of the genus in Turkey.…”
Section: Introductionmentioning
confidence: 99%